Hate Speech di Indonesia: Bahaya dan Solusi - Irawan Irawan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2018)
This article aims to explain hate speech in Indonesia and its solution. The theory used in this article is Critical Race Theory which is initiated by Richard Delgado and Jean Stefancic. This Critical Race Theory is also sustained by an Islamic perspective so as to be found the causes of hate speech and solutions that must be done. This paper concludes that: First, hate speech in Indonesia is verbally and non-verbally done which is delivered both directly and indirectly (social media). Second, hate speech in Indonesia causes social inequality, non-respectful attitudes, and national decline. Third, hate speech does not reflect the character of the Indonesian people who uphold ethics and the values of nationalism. Fourth, hate speech triggers violence and intolerance of religions, ethnicities, races, and groups. Hate speech must be jointly solved by government, religious leaders and society.